Effects of Different Polar Solvents Extraction on Functional Components and Their Antioxidant Activities of Sanghuangporus vaninii - Qi ZHANG; Chaomin YIN; Hong GAO; Xiuzhi FAN; Defang SHI; Sheng CHEN; Jifa LIU; Jianhua XU; Zhenshun LI (Shipin gongye ke-ji)
To clarify the effects of different polar solvents extraction on the functional components and antioxidant activities of Sanghuangporus vaninii, the crude polyphenols from the dried powder of S. vaninii were extracted with four different solvents (ethanol, acetone, ethyl acetate and compound solvents), the bioactive ingredients, polyphenol compositions and antioxidant activities of different extracts were measured and their correlation were analyzed. Results indicated that the yield, the total contents of polyphenols and triterpenoids in acetone extract (AE) were 12.91%, 37.38% and 8.11%, respectively, which were significantly higher than other extracts (P<0.05). The total flavonoid content of ethanol extract (EE) was 14.90%, which was higher than that of AE, ethyl acetate extract (EAE) and mixed solvent extract (MSE). The highest total sterol content was observed in EAE with the value of 12.61%. Interestingly, AE showed the highest content of protocatechuic aldehyde, protocatechuic acid, caffeic acid and p-coumaric acid with the values of 602.09, 90.25, 6.24, and 5.57 μg/100 mg, respectively. Its total content of phenolic acids were significantly higher than those in EE, EAE and MSE (P<0.05). In addition, AE demonstrated better ABTS+ radical scavenging and lipid peroxidation inhibition capacities than those of EE, EAE, and MSE. Its reducing power and protein oxidative damage inhibition capacities were significantly higher than those of EE, EAE, and MSE (P<0.05). Moreover, the DPPH radical scavenging and β-carotene-linoleic acid oxidation inhibition capacities of EAE were higher than those of EE, AE, and MSE. Its hydroxyl radical scavenging and DNA oxidative damage protection ability were significantly higher than that of EE, AE and MSE (P<0.05). There was a strong correlation between the content of polyphenols and the antioxidant activity. In summary, acetone solvent exhibited a higher extraction yield and higher content of main polyphenols components from S. vaninii, and the extract showed a good antioxidant capacity. The results will provide a theoretical basis for the development and utilization of S. vaninii products.